A conceptual framework for the South African fintech ecosystem - Masangwana, Vuyelwa (My University, 2021)
The term ‘ecosystem’ is synonymous with multi-company dynamic teamwork and a new way of organised economic activities. It is thus important to understand the modes of interaction among the heterogeneous actors in the ecosystem. Financial Technology (FinTech) became prominent after the financial crisis when the financial industry's role in economic growth became a global concern. Many FinTech companies were established by bankers who found themselves unemployed after the financial crisis and found creative ways to use their skills in financial services. The purpose of FinTech companies in the economy became pre-eminent due to their ability to reduce economic risks and costs through innovation. It also became clear that FinTech would benefit the financial system due to its efficiency in addressing transaction costs, information asymmetry and in addressing issues of taxation. No market player can afford to operate in a silo in the digital age, as collaboration and partnerships are more critical than ever. According to the IMF website (2020), South Africa is a dual economy and has one of the highest inequality levels worldwide. According to a Business Technology article published in 2019, there is still an untapped consumer opportunity, as there are nearly 1.2 billion people globally who do not have bank accounts. South Africa has a large unbanked or underbanked population, estimated to be about 11 million people. A healthy FinTech ecosystem will develop in South Africa if there is an improvement on barriers to entry and a better understanding of the consumer. The study aimed to establish whether the existing FinTech ecosystem models are suitable for the South African context and identify any discrepancies and similarities between developed and developing world FinTech ecosystem models. Qualitative research in the form of semi-structured interviews was conducted. The sample included 12 executives from South Africa who represented entrepreneurs and start-ups, policymakers and financial institutions. The sampling technique was purposive in nature, and it was chosen because of its convenience. The study found that an additional function of funding must be explicitly specified as a government role in the South African context. In addition, the study revealed that in the South African sense, customers must be segmented further to include the unbanked and underbanked market. There is no existing FinTech ecosystem model for South Africa, and this study has developed a model that suits developing countries, specifically South Africa. Finally, the study ii uncovered that incubation and mentorship are essential components of the FinTech ecosystem in South Africa. The study will assist policymakers and other FinTech ecosystem players to gain a better understanding of their roles and how they can contribute and collaborate to make the FinTech ecosystem a success. The study will also aid policymakers and FinTech companies to focus on consumers and help policymakers consider some of the frustrations that participants have raised about policies. It will further assist them in FinTech policy formulation and amendment of the existing or the creation of new policies and legislation.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Digital Business to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2021
Keywords: Financial technology; FinTech ecosystems; Funding and coordination; UCTD; SDG-8: Decent work and economic growth